Polymeric Nanoparticles for Biomedical Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Recently, polymeric nanoparticles (NPs) have attracted significant attention in biomedical applications. Due to their advantageous properties, including biodegradability, biocompatibility, and non-toxicity, natural and synthetic polymers are versatile materials that offer several advantages for the therapy and diagnosis of a vast range of diseases and health conditions. Encapsulating therapeutic agents in polymeric NPs allows for sustained drug release, which improves drug efficacy and safety, reduces unwanted side effects, and enhances patient acceptance and compliance. This Special Issue presents the most recent insights on advanced polymeric NPs and their current applications in healthcare, including the prevention, diagnosis, and treatment of diseases.